PENGARUH APLIKASI BEBERAPA ANDAM SERESAH TANAMAN TERHADAP PERKEMBANGAN DAN PENDAPATAN HASIL TANAMAN KACANG PANJANG (VIGNA UNGUICULATA SSP) VARIETAS PARADE: Kacang Panjang, Andam, Sekam, Mahoni - Suhardjito, Suhardjito (innofarm, 2025)
This application trial aims to determine the impact of several of the best plant litter andams on the development and income of long beans. The test was implemented in Ngawi City, Katikan Village, Kedunggalar District from November 2024 to February 2025. This test was implemented with RAK ​​(Randomized Block Design) with 7 plant litter andam treatments and 4 reviews (r). From the trial, it was found that the use of plant litter andam could significantly increase plant height, number of fruits per plant, fresh fruit weight per plant. The treatment of stem andam plus soybean leaves, rice straw, mahogany leaves was better than johar wood andam (Cassia Siamea Lingk), coconut fiber, cassava stems (Manihot Esculanta) and treatment without andam, because it could increase the development and income of long beans, increased yields on stems + soybean leaves 78%, on rice husk andam 62%, and mahogany leaf andam 54% compared to the control.